Evolving Dynamics of Civil Islam in Post-Reformation Indonesia: Balancing Democratic Aspirations and State Authority - Mikail, Kiki; Jody, Jeniwaty Moh (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
This article investigates the complex relationship between civil society, democratization, and civil Islam in Indonesia, focusing on the Reformasi era. It argues that civil society plays a vital role in promoting democratic governance and is crucial for the establishment and sustainability of democratic institutions. The study explores whether Islam can act as a driving force for progressive political change. Through a qualitative case study approach, the dynamics of civil Islamic movements and their interaction with Indonesia’s democratization process are examined. The findings indicate that civil Islam serves as a counterbalance to state power, advocating for justice, tolerance, and social rights. The study highlights how Indonesia’s interpretation of civil Islam, shaped by local socio-political contexts and cultural values, differs from Western notions of civil society. While civil Islam has significantly contributed to democratization, it continues to face challenges, including the threat of co-optation by political elites. The article emphasizes the need for a robust civil society that promotes autonomy and public participation, enabling civil Islam to play a critical role in supporting democracy and ensuring governance that reflects the aspirations of the Indonesian people.